Optimizing Oil Well Cementing: Effects of Dispersant and Fluid Loss Additive Concentrations on Thickening Time and Free Fluid Formation - Momoh abdulazeez adeyem; Akuma Oji; John Anaele; Nnadikwe Johnson (Jurnal Teknik Indonesia, 2026)
Optimising cement slurry properties through appropriate additive selection is critical for ensuring successful zonal isolation and preventing costly wellbore failures in oil and gas operations. This research investigated the effects of dispersant and fluid loss additive concentrations on the thickening time and free fluid formation of Class G cement slurry. A systematic two-factor three-level (3²) factorial design was employed, generating nine experimental runs. Statistical analysis included correlation analysis, ANOVA, and multiple regression modelling. The results revealed that dispersant concentration exhibited the strongest influence on thickening time behaviour, establishing it as the primary control mechanism for cement slurry pumpability. Fluid loss additive concentration demonstrated dual functionality, serving both as an effective filtration control agent and providing secondary influence on thickening time. Significant interaction effects were observed between dispersant and fluid loss additive concentrations (p = 0.040), indicating synergistic behaviours. Multiple regression analysis yielded highly predictive models for both response variables, with R² = 0.981 for thickening time and R² = 0.845 for free fluid. The developed models provide a systematic framework for cement slurry optimisation in oil well cementing operations, enabling precise targeting of cement slurry properties for improved well integrity and performance. The research demonstrates the effectiveness of factorial experimental design methodology for understanding complex additive interactions in cement slurry systems.